Quality by design (Qbd) approach to develop stability indicating HPLC method for estimation of rutin in chitosan-sodium alginate nanoparticles - Surendran Vijayaraj; Narahari N Palei; Devalapalli Archana; Kuppam Lathasri; Ponnusamy Rajavel (Universidade de São Paulo, 2021)
Rutin is a flavonoid glycoside, mainly consists of phenolic compounds, responsible for many biological activities. The objective of the present study was to develop and validate a precise, simple, robust, rapid and reliable reverse phase high -performance liquid chromatography (RP-HPLC) technique by using Qbd approach for evaluating the rutin in nanoparticles. Central composite design (CCD) was employed for optimizing the experimental conditions of RP-HPLC method. Buffer pH, methanol content in the mobile phase composition, flow rate, and wavelength were selected as independent variables whereas retention time, peak area, and asymmetry factor was selected as dependent variables. The retention time, peak area and asymmetric factor of rutin by using optimized independent variables were found to be 3.75 min, 1014.79 mV, and 1.26 respectively. The limit of detection and limit of quantitation values were found to be 0.005 µg/mL and 0.15 µg/mL respectively. For confirming linearity, accuracy, precision, and robustness, the optimized assay condition was validated as per ICH guidelines. The proposed method, which was optimized by QbD approach was found to be a suitable method for analyzing the rutin in chitosan-sodium alginate nanoparticles.